Workplace delivery of a dietitian‐led cardiovascular disease and type 2 diabetes prevention programme: A qualitative study of participants' experiences in the context of Basic Needs Theory. Issue 4 (10th November 2017) - Di Battista, E. M.; Bracken, R. M.; Stephens, J. W.; Rice, S.; Thomas, M.; Williams, S. P.; Mellalieu, S. D.; ,
Abstract: The Medical Research Council recommends strong theoretical underpinning in the design and evaluation of lifestyle intervention programmes (LIPs). This qualitative study aimed to use Basic Needs Theory (BNT) as a framework to explore participants' perspectives on a workplace dietitian‐led LIP. Specifically, experiences with LIP engagement and initiation and maintenance of behaviour change were evaluated. Fifteen semi‐structured face‐to‐face interviews were conducted with participants who had previously completed a workplace cardiovascular disease and type 2 diabetes prevention programme, which involved advice and motivational support with making dietary and lifestyle changes. Interviews were audio recorded and transcribed verbatim. To evaluate the narrative, interpretative phenomenological analyses were used with BNT as the theoretical framework. A total of 12 themes were identified in relation to the three concepts of BNT – autonomy, competence and relatedness – and organised into three domains: intervention engagement, behaviour change initiation and behaviour change maintenance. Line manager and colleague support to attend was reported to have a strong influence on intervention engagement, and the importance of dietitian and peer guidance in initiating behaviour changes was highlighted. Differences between participants who maintained behavioural changes compared to those who relapsed included autonomously seeking support (relatedness) through family, friends, healthcare professionals and commercial slimming organisations. BNT provided an insightful theoretical framework to evaluate factors that underpinned the effectiveness of a dietitian‐led cardiovascular and type 2 diabetes prevention LIP. Attendance and retention in workplace LIPs can depend on participants' managerial and colleague support, so recruitment processes should consider targeting managers in marketing and promotional activities. Workplace LIPs may increase the likelihood of behaviour change maintenance by including methods that foster longer term participant relatedness and emotional support.